Availability of business services and outward investment: Evidence from French firms - Holger Görg; Liza Jabbour (Kiel Institute for the World Economy (IfW), 2015)
This paper considers the link between the local availability of services and a firm's decision to become a multinational. This is a highly topical issue, given that many industrialised countries are increasingly becoming services economies and firms become increasingly more globalised. In an analysis of rich firm level data for France we find evidence that the availability of services in the home country indeed has a positive impact on firms' decisions to become multinationals. This is robust to endogeneity concerns. The result can be interpreted in a simple set up where the local availability of business services improves firm efficiency and, hence, allows firms to overcome sunk costs of investing abroad more easily.
Keywords: F23; R11; 330; Business Services; Foreign Direct Investment; Multinationals